PSYCHOLOGICAL EMPOWERMENT AND ORGANIZATIONAL COMMITMENT: EVİDENCE FROM THE TOURİSM INDUSTRY IN TURKEY - KAYA ÖZBAĞ, Gönül; POLAT ÜZÜMCÜ, Tülay (PEARSON JOURNAL, 2021)
ABSTRACT Purpose: This study intends to explore the link between psychological empowerment (PE) and organizational commitment (OC) with the data obtained from tourism sector employees in Turkey. Accordingly, the goals of the study are: i) To measure the level of OC (affective, normative and continuance commitment) among employees in the tourism sector in Turkey ii) To measure the level of PE (meaning, competence, self-determination and impact) iii) To examine the relationship between PE and OC. To test the proposed relationship, three hypotheses are developed; H1: PE will have a positive impact on affective commitment. H2: PE will have a positive impact on normative commitment. H3: PE will have a positive impact on continuance commitment. Research Methods: Each variable was measured using a 5-point Likert scale ranging from “strongly disagree” (1) to “strongly agree” (5). PE was measured by 12 items developed from the study of Spreitzer (1995). OC was measured by 9 items developed from the study of Meyer & Allen (1997). The data of the study were obtained both through the questionnaire technique via Google form and face to face interviews. Of the 118 respondents 80(68%) were men, and 38 (32%) were women. The majority of the participants (45%) are ranged in age from 17 to 25 years. Of the participants, %31 have üniversity educations and %46 have been working between 3 and 5 years in the company. The majority of the participants have an income ranging from 4001-6000 ? (Turkish Liras) where the net minimum wage is wage for single people is 2,826 ? (377) a month. Data from 118 employees have been evaulated by using of the SPSS 20.0 program Results and Discussion: The findings of the study reveal that the level of AC (mean = 3,81), NC (mean = 3,53), and CC (mean = 3,82) is moderate among tourism sector employees. Continuance commitment appears to be the highest of the three components of the OC which is not surprising as the respondents of the survey are from Turkey which has high unemployment rate (13,4 percent in February of 2021). In high unemployment work environments employees are likely to exhibit higher levels of CC because of the higher penalty of job loss. In such environments feelings of job insecurity among employees creates an incentive to embrace their current employment and thus they remain loyal and committed to their organization(Shapiro-Stiglitz, 1984). In terms of the correlations between the variables, the results reveal that all of the variables show significant positive correlations. On the other hand the findings indicate employees in tourism sector felt that they are not empowered enough by their organization (mean = 2,65). that the level. This result suggests that although employee empowerment is proved to be a useful tool, managers are resistant to share their power. Overall, consistent with other studies (Joo et al., 2010; Choong et al., 2011; Rawat, 2011; İbrahim, 2020), findings of the study indicate that PE has positive and significant impacts on AC (ß = .31, p< .01), NC (ß = .26, p< .05), CC (ß = .21, p< .05). Therefore it is evident that there is a need to improve the current situation at tourism companies with respect to all the components of the PE which in turn would enhance OC levels of employees. Implications: This research suggests that employees’ empowerment experiences directly affect their commitment level and thus in order generate high degree of OC, the tourism companies should develop training programs to foster managers in understanding appropriate practices and behavior sets that will enhance employee empowerment. However, it is useful to evaluate the results of the research in consideration of some constraints. First of all, the present study is carried out in Turkish companies in the tourism sector and the sample size is quite small. Therefore, one may debate that generalization of the results is questionable. Future research should observe a broader set of in order to identify if any the differences exist in relation to the characteristics of its industry. Researchers should also look to impact of leadership styles, ethical climate, corporate reputation on OC.